2011
DOI: 10.1210/en.2010-1398
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Modulate Structure and Function of the Suprachiasmatic Nucleus Brain Clock

Abstract: Gonadal hormones can modulate circadian rhythms in rodents and humans, and androgen receptors are highly localized within the core region of the mouse suprachiasmatic nucleus (SCN) brain clock. Although androgens are known to modulate neural plasticity in other CNS compartments, the role of androgens and their receptors on plasticity in the SCN is unexplored. In the present study, we ask whether androgens influence the structure and function of the mouse SCN by examining the effects of gonadectomy (GDX) on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 68 publications
(65 reference statements)
1
60
0
1
Order By: Relevance
“…Previous work has already demonstrated that handling can interact with the effects of ovarian hormones to impact hippocampus sensitive behaviors (Bohacek and Daniel, 2007), so the effect of ovarian hormones on Per1 expression needs to be explored in future experiments. Indeed, Per1 expression in the suprachiasmatic nucleus brain clock has been shown to be sensitive to circulating androgen levels (Karatsoreos et al, 2011), raising the possibility that steroid hormones can have modulatory effects on Per1 expression in different brain regions, possibly in concert with stress-hormones. Importantly, the present work used naturally cycling females, without controlling for the hormonal fluctuations occurring across the estrous cycle that may affect the responsiveness to stress (Figueiredo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has already demonstrated that handling can interact with the effects of ovarian hormones to impact hippocampus sensitive behaviors (Bohacek and Daniel, 2007), so the effect of ovarian hormones on Per1 expression needs to be explored in future experiments. Indeed, Per1 expression in the suprachiasmatic nucleus brain clock has been shown to be sensitive to circulating androgen levels (Karatsoreos et al, 2011), raising the possibility that steroid hormones can have modulatory effects on Per1 expression in different brain regions, possibly in concert with stress-hormones. Importantly, the present work used naturally cycling females, without controlling for the hormonal fluctuations occurring across the estrous cycle that may affect the responsiveness to stress (Figueiredo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of an essentially parallel literature on reproductive hormones and clock genes (Nakamura et al, 2008;Nakamura et al, 2010;Karatsoreos et al, 2011) again demonstrate the present minimal awareness of the functionally important adjacent positions of sex hormones and TNF in the same regulatory pathway. Certain clock genes have been demonstrated to undergo insulin-dependent regulation (Tahara et al, 2011), and to control adult neurogenesis, including in the hippocampus (Moriya et al, 2007;Borgs et al, 2009;Kimiwada et al, 2009), as well as endothelial cell (Wang et al, 2008) and cartilage (Mengatto et al, 2011) progenitors.…”
Section: B Clock Genes Controlled By Tumor Necrosis Factor Govern mentioning
confidence: 95%
“…This relationship became more provocative as they demonstrated that androgen administration in male mice can affect the molecular responses to time cues within the SCN, including immediate early gene expression (27), and in the current study, the induction of clock genes and structural plasticity (9). Finally, in this current study, they find that androgens are able to alter a potential physiological correlate of oscillator coupling, the proliferation of glial cells (9). This finding is consistent with their earlier behavioral results, indicating that androgens enhance rhythm precision (27) because models suggest that rhythm precision benefits from enhanced oscillator coupling.…”
mentioning
confidence: 72%
“…1). However, to our knowledge, the recent series of papers by the group of Silver and colleagues (4, 27, 28), including the current paper in this issue of Endocrinology (9), is the first to present a compelling story tracing the effects of reproductive hormones on SCN physiology through molecular mechanisms to functional organization and organismal outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation